Comprehensive Review of COVID-19 on Benign Prostate Hyperplasia Patient Symptoms - Joongwon Choi; Hong Jin Suh; Dong Hwan Lee; Tae-Kon Hwang; Jung Jun Kim (Urogenital Tract Infection)
Since the outbreak of the global Coronavirus disease (COVID-19) pandemic in 2019, the number of confirmed cases has increased steadily worldwide. The most common symptom of COVID-19 (SARS-CoV-2) is respiratory symptoms. On the other hand, increased voiding frequency and lower urinary tract symptoms (LUTS) have also been reported. Regarding the relationship between LUTS and COVID-19, only small size (n<100) retrospective studies have been reported, but the post-International Prostate Symptom Score (IPSS) increases compared to pre-IPSS after a COVID-19 infection in those older than 50 years. α-blockers and phosphodiesterase-5 inhibitors are relatively safe, but there are conflicting reports on 5α-reductase inhibitors; hence, further research is needed. Four major theories have been argued regarding the relationship between LUTS and COVID-19: renin-angiotensin system-related, androgen-related, inflammation-related, and metabolic derangement-related. In conclusion, elderly male patients often have benign prostate hyperplasia as a co-morbidity, and the severity of COVID-19 is high in this group. Therefore, voiding symptoms in these patient groups is of particular concern.